Clinical data-driven finite element analysis of the kinetics of chewing cycles in order to optimize occlusal reconstructions: dedicated to Professor Karl Stark Pister for his 95th birthday - Martinez Choy, Simon Ernesto; Lenz, Jürgen; Schindler, Hans; Wendler, Willi; Rues, Stefan; Schweizerhof, Karl; Terebesi, Sophia; Giannakopoulos, Nikolaos Nikitas; Schmitter, Marc (Computer modeling in engineering & sciences, 2021)
The occlusal design plays a decisive role in the fabrication of dental restorations. Dentists and dental technicians - depend on mechanical simulations of mandibular movement that are as accurate as possible, in particular, to - produce interference-free yet chewing-efficient dental restorations. For this, kinetic data must be available, i.e., - movements and deformations under the influence of forces and stresses. In the present study, so-called functional - data were collected from healthy volunteers to provide consistent information for proper kinetics. For the latter - purpose, biting and chewing forces, electrical muscle activity and jaw movements were registered synchronously, - and individual magnetic resonance tomograms (MRI) were prepared. The acquired data were then added to a - large complex finite element model of the complete masticatory system using the functional information obtained - and individual anatomical geometries so that the kinetics of the chewing process and teeth grinding could be - realistically simulated. This allows developing algorithms that optimize computer-aided manufacturing of dental - prostheses close to occlusion. In this way, a failure-free function of the dental prosthesis can be guaranteed and its - damage during usage can be reduced or prevented even including endosseous implants.